Experimental Investigation for a Novel Prototype of a Thermoelectric Power Generator With Heat Pipes - Liu, Yan; Shi, Zhaochun; Wang, Guohua; Yan, YuYing; Zhang, Yingchao (Frontiers in Energy Research, 2021)
In order to obtain the power generation of thermoelectric power generator (TEG) group, a similar structure of the disc sandwich structure and an experimental system are built to analyze the power generation performance and temperature characteristics. For improving heat transfer and migrating cold side and hot side. Two heat pipe columns as a connection are set between the TEG sides and fluid. The similar sandwich structure has 17 cold plates and 17 hot plates for the TEG pieces which are connected in series on the circuit. Working conditions are hot air flow and cold water flow. Hot air temperature and cold water temperature are set to a fixed temperature. The power generation of a single TEG is tested for verifying linear changes in the power generation performance with temperature differences (Td). Experimental results that the power generation is improved by the air flow and water flow increasing. The water flow has a smaller effect on the power generation than the air flow. In the cold side of TEG pieces, the cold side temperature is showed a gradual upward trend. The hot side temperature is showed a wave trough phenomenon. And the Td is showed a wave trough phenomenon. The hot air flow changing and the cold water changing cannot weaken the temperature trend of the hot side and cold side. And the hot air flow can significantly increase the Td than the cold water.